2011
DOI: 10.7454/mst.v14i2.692
|View full text |Cite
|
Sign up to set email alerts
|

DYE SENSITIZED SOLAR CELL WITH CONVENTIONALLY ANNEALED AND POST-HYDROTHERMALLY TREATED NANOCRYSTALLINE SEMICONDUCTOR OXIDE TiO2 DERIVED FROM SOL-GEL PROCESS

Abstract: Dye-sensitized solar cell (DSSC) is one of the very promising alternative renewable energy sources to anticipate the declination in the fossil fuel reserves in the next few decades and to make use of the abundance of intensive sunlight energy in tropical countries like Indonesia. In the present study, TiO 2 nanoparticles of different nanocrystallinity was synthesized via sol−gel process with various water to inorganic precursor ratio (R w ) of 0.85, 2.00 and 3.50 upon sol preparation, followed with subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…A hydrothermal treatment was applied here to prepare TiO2 anatase [instead of the supercritical extraction (SCE) method] because it offers several advantages, including high purities, a good distribution of the material, and increased photoactivity and crystallite size (Dai et al, 2010). Earlier studies on hydrothermal synthesis have shown good results for titanium-tetraisopropoxide, which exhibited an open circuit voltage of 69.33 mV and a crystallite size of 12.46 nm (Yuwono et al, 2010). In contrast, the SCE technique involves CO2 as the extraction solvent, which has the potential to augment the surface area of the nanoparticles but may also lead to a low degree of crystallinity.…”
Section: Introductionmentioning
confidence: 99%
“…A hydrothermal treatment was applied here to prepare TiO2 anatase [instead of the supercritical extraction (SCE) method] because it offers several advantages, including high purities, a good distribution of the material, and increased photoactivity and crystallite size (Dai et al, 2010). Earlier studies on hydrothermal synthesis have shown good results for titanium-tetraisopropoxide, which exhibited an open circuit voltage of 69.33 mV and a crystallite size of 12.46 nm (Yuwono et al, 2010). In contrast, the SCE technique involves CO2 as the extraction solvent, which has the potential to augment the surface area of the nanoparticles but may also lead to a low degree of crystallinity.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, the oxide should be nanocrystalline and have large surface area to enhance the light capturing and to facilitate the interaction between photon and dye solution. The previous work on TiO 2 nanoparticles with different nanocrystallinity for DSSC via sol-gel route was conducted by Yuwono et al [2]. The ratio of water to precursor or hydrolysis ratio, R w , used in their work were 0.85; 2.00, and 3.50.…”
Section: Introductionmentioning
confidence: 99%
“…Even so, agglomeration is most likely to happen because of the high overall surface energy causing a low crystallinity level, hence it results in non-optimal optical properties, including low level photon absorption (Wang, 2004). Additionally, Yuwono et al (2010; have made an effort to improve the crystallinity of TiO 2 and ZnO nanoparticles using posthydrothermal treatment (PHT), which is a water vapor treatment to break down the agglomeration and rearrange the inorganic framework of nanostructured materials, resulting in a much greater crystallinity. Based on their research, an increase in temperature of the posthydrothermal treatment has been found to increase the crystallinity of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc oxide (ZnO) is one of important materials which has been gaining special attention for various strategic applications, including solar energy to electrical conversion in dye-sensitized solar cell devices, photocatalysts, and optoelectronics (Kołodziejczak-Radzimska & Jesionowski, 2014;Yuwono et al, 2010). Various methods have been used to synthesize ZnO nanoparticles, such as precipitation (Srivastava et al, 2013), solgel (Yuwono et al, 2010), hydrothermal (Wen et al, 2014), and chemical bath deposition . In these previous studies, ZnO nanoparticles were synthesized using the precipitation method, considering its low cost and high purity level of the resulting product.…”
Section: Introductionmentioning
confidence: 99%